Determination of sinapine in rapeseed pomace extract: Its antioxidant and acetylcholinesterase inhibition properties. (15th March 2019) - Yates, Kyari; Pohl, Franziska; Busch, Maike; Mozer, Annika; Watters, Louis; Shiryaev, Andrey; Kong Thoo Lin, Paul
Highlights: Quantitative determination of bioactive sinapine in rapeseed pomace (RSP) extract. Anti-oxidant/radical scavenging properties of sinapine at RSP extract concentration. DNA protective properties of sinapine against free radical inducer. Sinapine inhibited AChE, a target for treatment of neurodegenerative diseases. RSP is a source of bioactive compounds for nutraceutical & pharmaceutical industry. Abstract: Sinapine is the main secondary metabolite present in rapeseed pomace (RSP) with its concentration being dependent on rapeseed processing, growing conditions, extraction parameters and the country of origin. Here we report, the concentration of sinapine from an extract of defatted RSP harvested in the North East of Scotland. Using liquid chromatography tandem mass spectrometry, the most abundant phenolic compound in the RSP extract was, as expected, sinapine (109.1 mg/g RSP extract). Additionally, sinapic, caffeic, ferulic and syringic acids were identified (0.159–3.91 mg/g RSP extract). Sinapine together with the phenolics at the concentration present in the RSP extract, exhibited ≥50% activity relative to the extract in antioxidant assays. Furthermore, sinapine provided plasmid DNA (pBR322) protection, from 2, 2′-azobis(2-amidinopropane) dihydrochloride and inhibited acetylcholinesterase activity by 85%. Molecular docking was utilised to explain the inhibitory activity. RSP can be an excellent source of bioactive compounds for pharmaceuticals, food additive and nutraceutical applications.